Analisis Rasio Laporan Keuangan Untuk Menilai Kinerja Keuangan Pada PT Bank SUMUT - Eva Malina Simatupang (JURNAL AKUNTANSI BARELANG, 2020)
This study aims to assess the financial performance of PT Bank SUMUT in terms of liquidity ratios, profitability ratios, and solvency ratios in period 2015-2017. The type of data used in this study is secondary data, that is balance sheet and income statement. Data collection in this study uses documentation and data processing techniques using ratio analysis techniques. The conclusion of this study is in terms of its liquidity ratio, PT Bank SUMUT's financial performance is quite good, in terms of its profitability ratio, PT Bank SUMUT's financial performance is not good, and in terms of its solvency ratio, PT Bank SUMUT's financial performance is quite good.